Morfo-anatomia, variabilidade química e atividade biológica do óleo fixo de sementes de apeiba tibourbou aubl. – malvaceae - Barros, Marilda da Conceição Ribeiro e (2010)
Apeiba tibourbou Aubl. is a arboreal plant found in Central America, northern Brazil to Minas Gerais and São Paulo. Is well distributed in the Central West region of Brazil. The oil from its seeds is used in Costa Rica to reduce hair loss and spasms treatments. This study aimed to perform a morpho-anatomic and histochemical leaves, flowers and fruit of Apeiba tibourbou and evaluate the physicochemical properties, lipid profile and power analgesic and anti inflammatory effect of the fixed oil from seeds by paw edema, formalin and carrageenan methods. Samples of leaves, bark, flowers and fruits were collected from five individuals (specimens). Samples were collected in the cities of Goiânia, Itauçu and Mossâmedes (Serra Dourada Environmental Reserve). Morphoanatomy leaves, flowers and fruits was performed by standard techniques. The fruits were manually benefited and the oil extracted was analyzed as to their physical-chemical properties and lipid profile. Samples of soil and leaves were collected and analyzed for the level of macro and micronutrients. Morphoanatomy showed anatomic patterns matching those already presented by other authors for Malvaceae. The following structures were observed: glandular and stellate trichomes were distributed by all organs of the plant. Secretory cavities present in almost all cross-sections performed. The average yield of the fixed oil of the seeds was 23.83%. The major constituent was 25.42% with lauric acid, found in all samples. Palmitic with 23.50% was the second major, linoleic acid, in third place with 11.51%. The fourth in per cent, with oleic acid and 9.30% in the fifth with -linolenic acid 8.11%. With 3.27% eicosapentaenoic acid (EPA) should also be considered the presence of docosahexaenoic acid (DHA) at 0.78%. In multivariate analysis of the organic-chemical and environmental data of leaves, soil and seed oil was observed that there is no change to oil chemistry regarding the environmental data. Regarding the analysis of biological activity of fixed oil of A. tibourbou, showed the same power and anti inflammatory analgesic method of writhing induced by acetic acid method of pain induced by formalin and paw edema induced by carrageenin. In this study, we observed that the oil of A. tibourbou presents as main constituent fatty acid omega 3, omega 6, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), lauric acid and palmitic acid. Can be used with food and medicinal purposes.